Usability analysis of advertising websites interfaces with the use of the universal design principles - Marciniec, Jan; Kondraciuk, Dominik (Journal of Computer Sciences Institute, 2023)
The aim of the research was to observe how the usage of the universal design principles influences on the accessibility and usability of websites. As one of the analysis’ subjects there was chosen the popular advertising website. It has been confronted with a newly implemented application offering the same functions, but improved with the requirements resulting from the universal design. In order to compare those two services there was conducted the study with the use of eye-tracking, LUT checklists and WAVE Evaluation Tool. These methods made it possible to demonstrate the differences between websites caused by the contrasting implementation methods. The results showed that an application of universal design principles has a positive impact on the websites’ accessibility and usability.